Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1037/spq0000434
|View full text |Cite
|
Sign up to set email alerts
|

Does the timing of kindergarten absences matter for children’s early school success?

Abstract: Although we know that children who are more frequently absent from school do less well academically, we know little about whether absences matter for other domains of development and whether the timing of their absences matter. In order to address these gaps in knowledge, we examined the experiences of 1,131 kindergartners (64% Hispanic, 7% Black, 17% Asian/other, 12% White) from a mid-Atlantic state. Covariateadjusted regression analyses showed that children who missed school more frequently did less well in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In the context of ECE, similar to correlates of teacher depressive symptoms, burnout has been found to predict lower instructional support among Head Start teachers (Sandilos et al, 2020). Another study showed that emotional exhaustion among teachers is related to lower-quality interactions with their students (Ansari et al, 2022). These findings highlight the negative outcomes of poor teacher well-being.…”
Section: Association Between Teacher Well-being On Teaching Adaptabilitymentioning
confidence: 83%
“…In the context of ECE, similar to correlates of teacher depressive symptoms, burnout has been found to predict lower instructional support among Head Start teachers (Sandilos et al, 2020). Another study showed that emotional exhaustion among teachers is related to lower-quality interactions with their students (Ansari et al, 2022). These findings highlight the negative outcomes of poor teacher well-being.…”
Section: Association Between Teacher Well-being On Teaching Adaptabilitymentioning
confidence: 83%
“…Additionally, applying adaptive coping strategies in the classroom can support teachers in coping with conflicts with students and pursuing high-quality relationship. Being able to cope with negative emotions and conflicts in interactions with students allows teachers to remain sensitive to the students' needs (Koenen et al, 2019b;Ansari et al, 2020b). During a conflict, teachers first need to cope with their own emotions before they are able to reconcile with the student and tend to the student's needs.…”
Section: Situation-specific Skillsmentioning
confidence: 99%
“…However, the negative impact of student absences on achievement may depend on the timing of absences within or across school years. A few studies have investigated whether absences have a different impact on children's achievement in end-of-year exams during different depending on when they occurred during the school year (Ansari et al, 2021;Chen et al, 2016; found that spring absences, as opposed to autumn absences, were associated with lower spring exam scores, with the 30-day window preceding the test being the most crucial.…”
Section: Introductionmentioning
confidence: 99%